1987
DOI: 10.1139/z87-353
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Plagiorchis noblei (Trematoda: Plagiorchiidae) matacercariae on the susceptibility of Aedes aegypti larvae to predation by guppies (Poecilia reticulata) and meadow voles (Microtus pennsylvanicus)

Abstract: Infection with the metacercariae of the digenean Plagiorchis noblei had no effect on the susceptibility of Aedes aegypti larvae to predation by guppies (Poecilia reticulata). In contrast, infected larvae were rendered more susceptible to being taken by meadow voles (Microtus pennsylvanicus) than were uninfected controls. Since voles, which will feed at the edge of water, are capable of supporting the adult fluke, transmission of the parasite to the definitive host may be facilitated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…A trematode using larval mosquitoes as an intermediate host, and requiring consumption of the mosquito by the definitive host, alters mosquito behavior to increase predation risk (138). In contrast, a nematode requiring survival of the mosquito for completion of development does not enhance antipredator responses of mosquito larvae to reduce predation risk (143).…”
Section: Predationmentioning
confidence: 99%
“…A trematode using larval mosquitoes as an intermediate host, and requiring consumption of the mosquito by the definitive host, alters mosquito behavior to increase predation risk (138). In contrast, a nematode requiring survival of the mosquito for completion of development does not enhance antipredator responses of mosquito larvae to reduce predation risk (143).…”
Section: Predationmentioning
confidence: 99%
“…In a more recent study, Moore ( 1983) demonstrated that starlings tended to feed preferentially on isopods infected with a larval acanthocephalan, Plagiorhynchus cylindraceus. Very recent work by Webber et al ( 1987) suggests that infection of mosquito larvae with metacercariae of the digenean Plagiorchis noblei does not influence susceptibility of infected mosquitoes to predation by guppies, but that infection increases susceptibility to predation by the vole definitive host, Microtus pennsylvanicus.…”
Section: Impact Of Infection and Disease On Individual Hosts Effects mentioning
confidence: 99%
“…Among the most dramatic effects of parasites are changes in the morphology, coloration, and behavior of their hosts (Oetinger and Nickol 1981, Moore 1983, Hurd 1990). These effects often are especially pronounced when the parasite requires transmission among hosts through the food chain in order to complete its life cycle (Webber et al 1987). In these instances, transitions in host phenotype are typically associated with the attainment of infectivity to the next host in the life cycle of the parasite, and the shifts in host phenotype can be interpreted as enhancing the effectiveness of transmission (Bethel and Holmes 1974, Poulin et al 1992, Tierney et al 1993, Robb and Reid 1996, Bakker et al 1997; but see Poulin 1995).…”
mentioning
confidence: 99%